Implementing Project-Based Learning Model (PjBL) to Develop Students' Writing Skills in Composing Academic Texts - Paris, Atika Salman; Hadi, M. Wahyu; Rosyidi, Ahmad Zuhri (Universitas Negeri Gorontalo, 2024)
This study aimed at enhancing students' ability to compose academic writing by implementing the Project-Based Learning (PjBL) model. The urgency of this research arises from the challenges faced by the students in academic proposal writing, often perceived as a major barrier in completing their education. The research method used is Classroom Action Research (CAR), divided into two cycles with stages of planning, implementation, observation, and reflection. The research subject comprises 22 seventh-semester students in the research proposal writing course at Institut Pendidikan Nusantara Global. The collected data through observation, interviews, and tests were then analyzed using descriptive qualitative methods. The result of the study indicated a significant improvement in proposal writing skills. In the pre-cycle stage, 36% of the 22 students were in the â€œsufficientâ€ category. After implementing the PjBL method in cycle I, there was an improvement with 43% of students in the â€œgoodâ€ category and 21% in the â€œvery goodâ€ category. In Cycle II, results improved further: 50% of students were in the â€œgoodâ€ category and 36% in the â€œvery goodâ€ category, while the â€œsufficientâ€ category dropped to 14%, with none in the â€œpoorâ€ category. This research shows that PjBL was effective in improving proposal writing skills, engaging students in critical and creative thinking, and strengthening written communication.